In Silico Characterization of Hemagglutinin Protein of Influenza a Virus [A/Canine/Beijing/Cau9/2009(H1N1] of H1N1 Subtype (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Using 3D-Jigsawn protein comparative modeling server, Verify-3D structure evaluation server, CHIMERA the homology modeling study of the mentioned protein was carried out and it holds the aim of the study. In this work, we in silico characterized the hemagglutinin protein of influenza A virus [A/canine/Beijing/cau9/2009(H1N1] (AEM89472). The model was validated by using protein structure checking tools RAMPAGE server for reliability. In NJ tree AEM89472 is place in a separate monophyletic and show close evolutionary relationship with ADD97678. Hex 6.3 was used for protein (Hemagglutinin) - ligand (Tamiflu) docking to determine the potential ligand binding sites. These ligand (Tamiflu) binding sites identified can provide an insight to design potential inhibitors in future.